Coleman's Singapore - Hancock, T.H.H. 1913- (Monographs of the Malaysian Branch, Royal Asiatic Society, 1986)
At first glance, the title of this book may appear to be an exaggeration: but if we remember that young Coleman arrived in Singapore when that spaesely populated settlement was only three years old, and that he not only surveyed the whole island and constructed inland roads and city streets, but also designed and erected many of the principal public and privately owned buildings in the urban area between 1828 and 1841, the reader will find little difficulty in accepting in accuracy.